Age-Dependent User Perception Analysis of Web Application Using Technology Acceptance Model Approach: A Case Study - Assaf Arief; Achmad Fuad; Suyuti; Suhartini (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
In the pursuit of technologically advanced governance, the Ministry ABC has integrated technology into daily operations, particularly through web applications like an employee administration information system. However, challenges persist in the implementation of online administration, especially in terms of technology adoption among the older generation. This study employs the Technology Acceptance Model (TAM) to investigate the usage of the administrative information system, focusing on System Quality (SQ), Perceived Ease of Use (EU), Perceived Usefulness (PU), and Behavioral Intention (BI). Surveying 147 respondents via questionnaires, the findings reveal that system quality positively influences perceived ease of use and perceived usefulness, while unexpectedly establishing a negative relationship between system quality, perceived ease of use, perceived usefulness, and behavioral intention. These insights hold significance for both theory and practice, reaffirming the crucial roles of perceived ease of use and perceived usefulness in shaping behavioral intentions and augmenting the TAM model.